A produção de conhecimento e a implicação para a prática do encaminhamento, diagnóstico e medicalização de crianças : contribuições da psicologia histórico-cultural - Colaço, Lorena Carrillo (2016)
The present research had as main purpose to understand the phenomenon of Medicalization, problematizing the contradictions that exist between the diagnosis and medication prescription to learning disorders and the knowledge production in the field of Medicine, Education and Psychology at Universidade de São Paulo (USP), from the Historical-Cultural Psychology referential. The focus was to investigate the relating between the scientific production and the practice in these three chosen areas. To do that, this research was split in two moments: first, in Section I, it was made a retrospective of the Attention Deficit Hyperactivity Disorder, since it appeared for the first time in the Diagnostic and Statistical Manual of Mental Disorders (DSM-III) on 1980, going through changes on DSM-IV on 1994, and then other ones on DSM-V, on 2013. After that, a documental research was done, where researches developed at Universidade de São Paulo, in the last 10 years - between the years 2005-2014 - highlighting the Attention Deficit Hyperactivity Disorder, were investigated. From the found papers, some points were detached: the difference between the prevalence data of ADHD, the diagnostic that was made through extremely quantitative evaluation and its consequences, among others. By the end of that, it was briefly detached the roll of the pharmaceutical companies on the knowledge production and the medication use. In Section II, it was presented several data about the diagnostic and the use of controlled medication by children from elementary school, at Maringá - PR (these data are part of a bigger project, called Projeto sobre Medicalização da Infância no Estado do Paraná, which several Universities, researchers and cities from Paraná are involved). In that stage, among the diagnostic assigned to the kids, the most frequent was the ADHD and among the medication, the one which is used the most is the Methylphenidate (known as Ritalin) which was associated to the use of other controlled medication, with cases where even five different drugs were used by the same child. As results, it was presented some authors that contribute to confront the phenomenon of medicalization of the scholar processes and a discussion about the disconnection between the scientific production and the acting of the professionals at the scholar context, detaching the critic studies found in the Psychology field, that studied cases of learning difficulties and the 'supposing' disorders and possible contributions to the teacher qualification.